2016
DOI: 10.1002/uog.15799
|View full text |Cite
|
Sign up to set email alerts
|

Placental histological patterns and uterine artery Doppler velocimetry in pregnancies complicated by early or late pre-eclampsia

Abstract: Objectives To study placental patterns in pregnancies complicated by pre-eclampsia (PE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 27 publications
3
34
1
3
Order By: Relevance
“…The authors concluded that prevalence was four‐ to seven‐fold higher in PE compared with normal pregnancies. These findings are consistent with our own, in which we identified qualitatively similar placental lesions in the total cohort of women affected by PE, although their incidence was quantitatively different according to gestational age (GA) at PE onset, with pathological placental changes being significantly more frequent in cases complicated by early‐onset PE (< 34 weeks' gestation (EO‐PE) as compared with those with late‐onset PE (> 34 weeks' gestation (LO‐PE)). We also tested the relationship between histopathological placental features and second‐trimester uterine artery (UtA) Doppler velocimetry.…”
supporting
confidence: 91%
“…The authors concluded that prevalence was four‐ to seven‐fold higher in PE compared with normal pregnancies. These findings are consistent with our own, in which we identified qualitatively similar placental lesions in the total cohort of women affected by PE, although their incidence was quantitatively different according to gestational age (GA) at PE onset, with pathological placental changes being significantly more frequent in cases complicated by early‐onset PE (< 34 weeks' gestation (EO‐PE) as compared with those with late‐onset PE (> 34 weeks' gestation (LO‐PE)). We also tested the relationship between histopathological placental features and second‐trimester uterine artery (UtA) Doppler velocimetry.…”
supporting
confidence: 91%
“…On the other hand, SGA cases with normal fetoplacental Doppler exhibited a higher prevalence of placental findings than did uncomplicated pregnancies. Additionally, UtA‐PI showed the ability to predict villous infarcts in PE. Overall, fetoplacental Doppler parameters seem to reflect placental vascular findings related to malperfusion.…”
Section: Discussionmentioning
confidence: 95%
“…The use of ultrasound as a tool for screening/prediction of PE is based on the fact that defective placentation results in incomplete transformation of the spiral arteries. Placental villous and vascular histopathological lesions are four‐to‐seven times more common in PE than in non‐PE pregnancies and are associated with increased resistance to uterine artery blood flow. Measurement of impedance (or resistance) to flow in the uterine arteries by Doppler assessment thus renders quantifiable the incomplete transformation of the spiral arteries.…”
Section: Screening For Pre‐eclampsia Using Ultrasoundmentioning
confidence: 99%